Effect of omega-3 and omega-6 fatty acid inclusion in broiler breeder’s diet on laying performance, egg quality, and yolk fatty acids composition - SABER, SEYYED NAEIM; KUTLU, HASAN RUSTU (The Indian Journal of Animal Sciences, 2018)
The present study was conducted to evaluate the effect of different dietary oil sources (omega-3 and omega-6 fatty acid) in female broiler breeders’ diets on laying performance, egg quality and yolk fatty acids composition. Ross-308 breeders (220; 25 weeks old) were used in this experiment for 6 weeks. Birds were placed in a complete randomized design with 4 dietary treatments (containing 2% soybean oil, 2% sunflower oil, 2% flaxseed oil, and 2% fish oil) and 5 replications containing 1 male + 10 females in each pen having a similar body weight (3,424 g) and egg production (86%). Results indicated that different sources of dietary oil had no significant effect on body weight gain, feed conversion ratio, and egg production but had a significant effect on egg weight. Also feeding the diets containing 2% of different fatty acids had a significant effect on some egg quality parameters and egg yolk fatty acids composition. It was concluded that inclusion of 2% flaxseed oil can improve laying performance, egg quality, and egg yolk fatty acids composition parameters in broiler breeders.